FORMULASI KEBIJAKAN PEMEKARAN WILAYAH DISTRIK DI PROVINSI PAPUA (KAJIAN TERHADAP PERATURAN PEMERINTAH NO. 17 TAHUN 2018) - Herman Ick; Yosephina Ohoiwutun (JURNAL KEBIJAKAN PUBLIK, 2021)
The purpose of this research is to highlight two things, namely, first, the issue of the process of determining the policy agenda for the expansion of districts in Papua Province. Second, the determinants that support and hinder the division of the District in Papua Province. The research method used is descriptive qualitative. With the research location in Papua Province. The technique of determining informants is carried out by snowball, for those who have knowledge of the proposed district expansion areas in Papua Province. Then, the data collection techniques used were observation and interviews, then the research instruments included, interview guides, and recording devices. Data analysis techniques through the stages of data categorization, data description and data interpretation. The results show that firstly, the preparation of the expansion policy agenda in Papua province, when viewed from the regulation of the Special Autonomy Law in general, contains the importance of reviewing aspects of the locality of Papua Province, therefore it is possible to produce affirmative policies as an alternative to contextualizing the locality with national policies related to expansion. District in Papua. Second, the supporting factor is that with a variety of resources owned, the state or government can provide opportunities to improve the quality of human resources in the regions, especially Papua Province through the policy of regional expansion. Then the inhibiting factor is the dilemma of the expansionary requirements and in fact contradicts the context of the Papua Province region.